KONVERGENSI EKOLINGUISTIK DAN FIQH AL BI’AH DALAM PELESTARIAN LINGKUNGAN - Akmaluddin Akmaluddin (Universitas Islam Negeri Mataram, 2020)
This article is motivated by several realities, namely: (1) Thereis a strong symptom of the uprooting of local wisdom values among theyounger generation. (2) There are symptoms of incompatibility betweenhuman relations and the environment that influence each other. (3) Theliveliness of regional languages which contains local wisdom values is due tothe influence of the domination of foreign languages. This reality needs tobe examined from an ecolinguistic perspective and fiqh al-bi’ah in an effortto conserve the environment. On this basis, this paper aims to explore theintersection between two interdisciplinary studies, namely ecolinguistics andfiqh al-bi’ah. The approach used in this research is descriptive comparativeapproach. This approach is used with the aim of providing a comparativepicture or description of a situation objectively viewed from different pointsof view. In this research, the connected object is the environmental realityin terms of interdisciplinary ecolinguistics and fiqh al-bi’ah. Sources of datain this study are linguistic realities related to environmental problems. Theresults of this study indicate that there are several forms of language that havethe potential to become extinct due to changes in interaction patterns withthe environment. In addition, undirected patterns of human interaction alsoresult in environmental damage. In line with the results of studies conductedby many researchers, this article concludes that the rules of fiqh al-bi’ah andecolinguistic concepts need to be used as a basis for interacting with theenvironment.